2011
DOI: 10.1124/dmd.111.042309
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cryopreserved HepaRG Cells with Cryopreserved Human Hepatocytes for Prediction of Clearance for 26 Drugs

Abstract: ABSTRACT:Prediction of clearance in drug discovery currently relies on human primary hepatocytes, which can vary widely in drug-metabolizing enzyme activity. Potential alternative in vitro models include the HepaRG cell (from immortalized hepatoma cells), which in culture can express drug-metabolizing enzymes to an extent comparable to that of primary hepatocytes. Utility of the HepaRG cell will depend on robust performance, relative to that of primary hepatocytes, in routine high-throughput analysis. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…The underprediction for CYP2D6 metabolized compounds in HepaRG™ has already been reported due to a CYP2D6-deficient donor (11,30,31). However, the fold of underprediction seems to vary between the applied enzyme markers due to potential metabolism by multiple CYP enzymes (11,(30)(31)(32). For example, the intrinsic clearances in HepaRG™ as compared to suspension cultures were decreased more for dextromethorphan and metoprolol than for propranolol (11,30).…”
Section: Metabolic Activity Assessment Of In Vitro Liver Models and Cmentioning
confidence: 82%
“…The underprediction for CYP2D6 metabolized compounds in HepaRG™ has already been reported due to a CYP2D6-deficient donor (11,30,31). However, the fold of underprediction seems to vary between the applied enzyme markers due to potential metabolism by multiple CYP enzymes (11,(30)(31)(32). For example, the intrinsic clearances in HepaRG™ as compared to suspension cultures were decreased more for dextromethorphan and metoprolol than for propranolol (11,30).…”
Section: Metabolic Activity Assessment Of In Vitro Liver Models and Cmentioning
confidence: 82%
“…[12][13][14][15] Furthermore, HepaRG cells have been shown to be quantitatively comparable to human hepatocytes for predicting the clearance of CYP drug substrates and as alternative in vitro tools. 16) Toxicological studies have reports the usefulness of HepaRG cells as in vitro hepatic models. 17,18) Several cytotoxicity and toxicogenomic studies have shown that HepaRG cells could be a more accurate human hepatocyte-like model than other hepatic cell lines and would be useful for toxicological studies.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%
“…Nonetheless, these developments do not have to restrain the quantitative use of Caco-2 results for chemicals that fall into the domain for which adequate in vivo predictive value is already obtained. Moreover, physiologically based kinetic computer modelling to integrate different types Zanelli et al, 2011). In addition, also the HepaRG cell line provides an adequate predictive value of in vivo metabolic clearance rates (r 2 = 0.53) (Zanelli et al, 2011), with a predictivity equal to that of cryopreserved primary human hepatocytes in the same study.…”
Section: In Vitro Methods For Intestinal and Liver Metabolismmentioning
confidence: 99%
“…Moreover, physiologically based kinetic computer modelling to integrate different types Zanelli et al, 2011). In addition, also the HepaRG cell line provides an adequate predictive value of in vivo metabolic clearance rates (r 2 = 0.53) (Zanelli et al, 2011), with a predictivity equal to that of cryopreserved primary human hepatocytes in the same study. In comparison to in vitro methods for absorption or luminal digestion, there is little use of in vitro metabolism data within the risk evaluations of food chemicals (11-17% of the evaluations contained such data) (Fig.…”
Section: In Vitro Methods For Intestinal and Liver Metabolismmentioning
confidence: 99%
See 1 more Smart Citation